Pembuatan Media Pembelajaran dengan Platform Educaplay pada Topik Freunde, Kollegen und Ich - Anita Simanjuntak; Herlina Jasa Putri Harahap (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The aim of this study is to develop learning media on the Educaplay platform on the topic „Freunde, Kollegen und Ich“. This study uses a qualitative approach and the development model based on the theory of Richey and Klein. This theory includes three phases: (1) planning, (2) creation, and (3) evaluation. The book Netzwerk neu A1 by Stefanie Dengler et al. (2021) was used as the data source in this study. The data consist of words, sentences, and grammatical rules at the A1 level taken from Chapter 2 „Freunde, Kollegen und Ich“, which appears on pages 18–27. The grammar topics covered in this chapter include: (i) irregular verbs and personal pronouns, (ii) yes/no questions, (iii) definite articles: der, die, das, (iv) nouns: singular and plural, and (v) the verbs haben and sein. The result of this study is a set of learning media on the Educaplay platform in the form of grammar exercises at the A1 level. The materials were validated by content experts based on five assessment criteria and scored 90 points, which corresponds to a very good rating. The Educaplay learning media was also validated by media experts and received a score of 90 points, also indicating a very good rating. Based on the findings of this study, the exercises developed on Educaplay can be used by lecturers and students as innovative and interactive learning media for A1 grammar.